Transdisciplinary competency-based development in the process engineering subjects: A case study in Brazil - de Oliveira, Roger Assis; Hipólito, Giovanna Milena Borges; Pontes, Ricardo de Freitas Fernandes; Ferreira, Paulo Henrique Nascimento; Moreira, Ricardo Sanz; Plácido, José; Silva, Carlos Alexandre Moreira da; Tovar, Laura Plazas (Education for chemical engineers, 2023)
Recently, the Brazilian Ministry of Education issued New Curriculum Guidelines for engineering programs. This paper encompasses a pedagogical intervention reflecting our efforts to incorporate these new guidelines into our engineering program. Specifically, this work has led to the competency-based rework of the following subjects offered in the Chemical Engineering Undergraduate Program at the Federal University of São Paulo (Unifesp): I) Modeling and Systems Analysis; II) Synthesis and Optimization of Chemical Processes; III) Chemical Process Simulation; IV) Process Analysis and Control; V) Chemical Process Design; and VI) Chemical Installations Design. Thirteen transdisciplinary competencies are integrated throughout the six subjects. Students highlighted design thinking, lifelong knowledge/learning, openness to act autonomously, teamwork, communication, and cooperation as essential qualities. Moreover, the greater focus on the process systems engineering approach involving the analysis, synthesis, design, and control of sustainable processes helps chemical engineers to face new challenges using renewable resources. •Pedagogical intervention on competency-based versus subject-based development.•Competencies development in Process Systems Engineering subjects.•Reformulation of development by competencies is endorsed by sustainable development.•Functional competencies listed improve attitude, skills, and knowledge of students.•Transdisciplinarity solutions respecting the environment and next generations.